2010
DOI: 10.1016/j.atherosclerosis.2009.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Periostin mediates vascular smooth muscle cell migration through the integrins ανβ3 and ανβ5 and focal adhesion kinase (FAK) pathway

Abstract: Smooth muscle cell (SMC) migration involves interactions of integrin receptors with extracellular matrix (ECM) and is an important process of neointimal formation in atherosclerosis and restenosis after vascular interventions. Previous studies have shown that periostin (PN), a novel ECM protein, is upregulated in rat carotid artery after balloon injury, and growth factor-stimulated expression of PN promotes SMC migration in vitro. Here, we address the mechanism by which PN-integrin interaction mediates SMC mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
123
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(134 citation statements)
references
References 36 publications
8
123
2
1
Order By: Relevance
“…Overexpression of periostin in aortic SMCs induced migration together with increased integrin-b3 expression and FAK phosphorylation. 7 In addition, periostin expression was increased in vascular SMCs subjected to mechanical strain, and this increase was followed by FAK activation and MCP-1 secretion, which were inhibited by a periostin-neutralizing antibody. 31 In agreement with these studies, induction of periostin in the NTS model was determinant for the de novo expression of integrin-b3 followed by downstream FAK and AKT activation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Overexpression of periostin in aortic SMCs induced migration together with increased integrin-b3 expression and FAK phosphorylation. 7 In addition, periostin expression was increased in vascular SMCs subjected to mechanical strain, and this increase was followed by FAK activation and MCP-1 secretion, which were inhibited by a periostin-neutralizing antibody. 31 In agreement with these studies, induction of periostin in the NTS model was determinant for the de novo expression of integrin-b3 followed by downstream FAK and AKT activation.…”
Section: Discussionmentioning
confidence: 96%
“…[3][4][5] Interaction of periostin with cell-surface integrins avb3 and avb5 has been associated with increased adhesion and migration of cancer cells and vascular smooth muscle cells (SMCs). 6,7 Periostin is highly induced in vitro by TGF-b1, 1,5,8 and it was also found to be upregulated by angiotensin II in cardiac fibroblasts. 8 IL-4 and IL-13 increased periostin in lung fibroblasts and bronchial epithelial cells, associating its induction with asthma.…”
mentioning
confidence: 99%
“…Recent reports have shown that the activation of FAK is essential for cell migration (11). To determine whether FAK has a role in ANG II-dependent SMC migration, we performed the scratch and Boyden chamber assays on SMCs treated with the FAK inhibitor, PF-573228, in the presence or absence of ANG II (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of FAK has been implicated in vascular cell migration, both in cardiovascular disease and in angiogenic vasculature that accompanies metastatic lesions; however, little is known about the mechanism of FAK activation in vascular SMCs (11,18). FAK has over 20 phosphorylation sites; however, Y 397 is considered the primary site and is activated by autophosphorylation (6).…”
Section: Discussionmentioning
confidence: 99%
“…Predominantly, periostin has been shown to mediate its effects through integrins (such as avb3) and adhesive signaling. [29][30][31][32] Although Nishiyama's proposal requires intracellular interactions between periostin and BMP-1, the ability of rhPN to increase MMP2 expression, thereby facilitating laminin5c2 cleavage, may represent an alternative mechanism for keratinocyte proliferation based on avb3 ligation and adhesion signaling. 14 As in the previous studies, a full-thickness excisional wound model was used, although it is unclear whether an 8 or 10 mm punch was used since both are stated in the methods (Table 1).…”
Section: Excisional Repair In the Postn 2/2 Mousementioning
confidence: 99%